Helicobacter pylori Induces Gastric Epithelial Cell Apoptosis in Association with Increased Fas Receptor Expression - Jones, Nicola L. (American Society for Microbiology, 1999)
The mechanisms involved in mediating the enhanced gastric epithelial cell apoptosis observed during infection with Helicobacter pylori in vivo are unknown. To determine whether H. pylori directly induces apoptosis of gastric epithelial cells in vitro and to define the role of the Fas-Fas ligand signal transduction cascade, human gastric epithelial cells were infected with H. pylori for up to 72 h under microaerophilic conditions. As assessed by both transmission electron microscopy and fluorescence microscopy, incubation with a cagA-positive, cagE-positive, VacA-positive clinical H. pylori isolate stimulated an increase in apoptosis compared to the apoptosis of untreated AGS cells (16.0% ± 2.8% versus 5.9% ± 1.4%, P < 0.05) after 72 h. In contrast, apoptosis was not detected following infection with cagA-negative, cagE-negative, VacA-negative clinical isolates or a Campylobacter jejuni strain. In addition to stimulating apoptosis, infection with H. pylori enhanced Fas receptor expression in AGS cells to a degree comparable to that of treatment with a positive control, gamma interferon (12.5 ng/ml) (148% ± 24% and 167% ± 24% of control, respectively). The enhanced Fas receptor expression was associated with increased sensitivity to Fas-mediated cell death. Ligation of the Fas receptor with an agonistic monoclonal antibody resulted in an increase in apoptosis compared to the apoptosis of cells infected with the bacterium alone (38.5% ± 7.1% versus 16.0% ± 2.8%, P < 0.05). Incubation with neutralizing anti-Fas antibody did not prevent apoptosis of H. pylori-infected cells. Taken together, these findings demonstrate that the gastric pathogen H. pylori stimulates apoptosis of gastric epithelial cells in vitro in association with the enhanced expression of the Fas receptor. These data indicate a role for Fas-mediated signaling in the programmed cell death that occurs in response to H. pylori infection.